Pengaruh Persepsi Harga, Kualitas Produk, Servicescape dan Word of Mouth terhadap Keputusan Pembelian di Grand Garden Resto dan Cafe - Sofyan Hartono; Leonardo Indra Vitaharsa (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The restaurant industry in Indonesia has experienced significant growth in line with economic development, urbanization, and changes in people's lifestyles. The increasing demand for restaurants is not only based on food quality but also on a comfortable and memorable dining experience. Various restaurant concepts have emerged to meet these needs, offering both local and international cuisine, supported by adequate facilities and professional service. Price perception, product quality, servicescape, and word of mouth are believed to influence purchasing decisions. The purpose of this study is to examine the effect of price perception, product quality, servicescape, and word of mouth on purchasing decisions at Grand Garden Resto and Cafe. This research adopts a quantitative approach. The sample consists of 150 individuals who have previously made purchases at the restaurant. The sampling method used is non-probability sampling with an accidental sampling technique. Data processing in this study was conducted using the SmartPLS application. The findings indicate that price perception, product quality, and word of mouth have a positive and significant influence on purchasing decisions, while servicescape does not affect purchasing decisions.